On generalized solutions of boundary value problems for some general differential equations - Burskii, V.P. (Нелинейные граничные задачи, 1999)
In this article we will introduce and consider a notion of generalized solutions of boundary value problems for the equations of the following general form ℒ⁺○ A ○ ℒu = f in arbitrary fixed domain Ω ⊂ Rⁿ